2002
DOI: 10.1046/j.1365-2427.2002.00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the responses of diatoms and macro‐ invertebrates to metals in upland streams of Wales and Cornwall

Abstract: SUMMARY 1. Surprisingly few data compare the apparent responses of diatoms and macroinvertebrates to metals in streams. We examined variation in metals, diatoms and macroinvertebrates between 51 streams in metal‐mining areas of Wales and Cornwall, U.K., using a survey design with multiple reference and polluted sites. 2. To quantify variations in metals between sites, we calculated cumulative criterion unit (CCU) scores, a recently defined measure of total stream metal concentration and toxicity, to account fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
2
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(89 citation statements)
references
References 72 publications
6
77
2
4
Order By: Relevance
“…As the criterion values are only available for individual elements, alternative models are necessary to estimate toxic effects of metal mixtures, hence the derivation of the CCU was used (Clements et al, 2000). The EPA metal thresholds considered are based on toxicity tests of species from different trophic levels, including macroinvertebrates (Hirst et al, 2002). The enrichment factors (CCU) calculated with respect to the EPA guidelines showed that the concentrations of Al, As, Cd, Cu, Fe, Mn, Ni, Pb and Zn were enriched and exceeded their maximum permissible levels (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the criterion values are only available for individual elements, alternative models are necessary to estimate toxic effects of metal mixtures, hence the derivation of the CCU was used (Clements et al, 2000). The EPA metal thresholds considered are based on toxicity tests of species from different trophic levels, including macroinvertebrates (Hirst et al, 2002). The enrichment factors (CCU) calculated with respect to the EPA guidelines showed that the concentrations of Al, As, Cd, Cu, Fe, Mn, Ni, Pb and Zn were enriched and exceeded their maximum permissible levels (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…This criterion has been already applied to analyse the response of different organisms to metals in streams (Clements et al, 2000;Hickey and Golding, 2002;Hirst et al, 2002). The authors have followed the USEPA chronic criterion values for Al (87 μg L −1 ), Fe and Mn (1000 μg L −1 ), whilst the criterion values for Ag (1.…”
Section: Stream Water Datamentioning
confidence: 99%
“…7 It is well known that high metal concentrations in aquatic ecosystems lead to a reduction of macroinvertebrate richness and abundance. 15,20,[36][37][38][39] In Brazilian streams, Chironomus and Odonata larvae can survive even in sites with very low environmental quality because they are tolerant to many disturbances. 20,40,41 Our results also show that it is possible to analyze metal concentrations in these aquatic macroinvertebrates even when the community is very poor, as occurs in sites near to the sugar cane culture…”
Section: Discussionmentioning
confidence: 99%
“…Zoobenthic forms, such as Crustaceae, insect larvae, and annelida, are often the main diet for many fish species (especially Cyprinids) and may contribute to the transfer of metals to higher trophic levels. Although, boron was found to be neither genotoxic nor carcinogenic for human health (WHO 1998b), and no negative effects of boron on reproductive health were found (Ş aylı et al 1998), it is well known that high metal concentrations in aquatic ecosystems lead to a reduction of macroinvertebrate richness and abundance (Watanabe et al 2000;Hirst et al 2002;Smolders et al 2003). This makes it possible to analyse metal concentration in this invertebrate even when the community is very poor as at some sites along the Emet and Orhaneli rivers.…”
Section: Resultsmentioning
confidence: 99%